The relationship between presbytery and clerical associations - Interguglielmi, Antonio (Prawo Kanoniczne, 2021)
Believers' right of association recognized through the second Vatican Council and translated in the Canon Law in 1983 concerns clerics as well. The letter may thus pursue interests buond to their ministry. This right needs to clarify the features of these associations which may neither be a kind of clerics'trade Union, in constrast with the authorities, nor a copy of the representative body, already provided by the CIC of the diocese, t.i., the presbyteral council. The present meditation on the relationship between presbytery and clerical associations represents a seminal aspect in order to understand both nature and function of the presbyteral ministry and the right relationship with the bishop within the particular church.